Arquiconfraria do cordão de São Francisco em Mariana: trajetória, devoção e arte (c. 1760-1840) - Maria Clara Caldas Soares Ferreira (2013)
The present dissertation has investigated the trajectory, devotional culture and artistic panorama of the Archconfraternity of the Cord of St. Francis, in the town of Mariana, in the 1760s and 1840s. The aspects related to the institution and development of this religious order were discussed based on a various range of documents produced both by the arch-confrères themselves and by monks and members of the Portuguese Crown. The characteristics of the rivalry held against the Third Order of Penance were ascertained, as well as the strategies adopted by the Cord in order to share the cult of St Francis in this locality. The research also examined the artistic and technical aspects of architecture and interior decoration of the Chapel of Our Lady of the Angels, demonstrating the uniqueness of the faith of the pardos and the intersection between devotion and skin color.